DRINKING WATER PROBLEM (Conference Zone, 2022)
The article deals with the issues of contamination of drinking water with various sources that cause deterioration in the quality of the habitat and affect the state of human health. The methods of drinking water purification are also considered and an assessment of the existing structure of drinking water supply systems is given